PENGEMBANGAN MODEL PERMAINAN SOCCER RAKET DALAM PEMBELAJARAN SEPAK BOLA PADA SISWA KELAS 6 SD NEGERI 01 TEMPELREJO KECAMATAN MONDOKAN KABUPATEN SRAGEN (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The method of research is the development of models of learning: (1) a preliminary investigation andinformation gathering, field observations and literature review, (2) develope early prodak form (the form offootball games soccer rules racket), (3) evaluation of the experts by using the penjas experts and the learning, aswell as small group trials, with the use of questionnaires and consultations and evaluations are then analyzed,(4) revision of the first product, and product revision based on the results of an expert evaluation and testing of asmall group. This revision is used for the improvement of the initial products made by researchers, (5) fieldtesting, (6) revision of the final product which is based on the results of field tests, (7) final football game ofsoccer modifications racket models for students 6th grade N Tempelrejo 01 generated by the revised field test.Data collection using questionnaires obtained from evaluation experts (one expert and one expert penjasLearning), a small test group (16 students sons and daughters of Class 6 SD N Tempelrejo 01), and field test(43 N 6th grade students Tempelrejo 01) . Data in the form of research on product quality, and productimprovement suggestions, and the results of the questionnaires by students. Technical analysis of the data usedis descriptive percentage to reveal aspects of cognitive, effective and psychomotor students after using theproduct.